Properties enhancement of oil palm trunk plywood against decay and termite for marine applications - Che Ismail, Atikah; Salim, Sabiha; Md Tahir, Paridah; Lee, Seng Hua; Abd Ghani, Muhammad Aizat; Al Edrus, Syeed Saifulazry; Ahmad Faisal, Fadhlin Qayyum (MDPI, 2022)
Oil palm trunk (OPT) veneers have the potential to be used in the production of plywood for marine applications. However, OPT is not resistant to fungal decay and termites, limiting its use in the production of marine plywood. As a result, in this study, phenolic resin treatment was used to improve the biological durability of OPT and produce marine grade equivalent (MGE) plywood. The OPT veneer was treated with medium molecular weight phenol formaldehyde (MmwPF) resin. The results showed that MmwPF resin with a solid content of 30% resulted in higher weight percent gain and polymer retention. Veneers treated with 30% MmwPF resin were then pressed for more than 10 min at temperatures above 140 °C. Dimensional stability, shear strength, bending strength, fungal decay resistance, and termite resistance were all tested on the plywood produced. The results of this study revealed that MGE plywood has satisfactory bonding quality and excellent biological durability. Good bending strength was recorded for the MGE plywood with modulus of rupture and modulus of elasticity ranged between 31.03 and 38.85 MPa and 4110 and 5120 MPa, respectively. Rubberwood, as a reference sample in this study, is not durable (Class 5) against white rot fungi and is moderately durable (Class III) against subterranean termite attacks. Interestingly, MGE plywood produced in this study was found very durable (Class 1) against white rot fungi. It is also durable (Class II) and very durable (Class I) against termite attacks, depending on the pressing parameters employed. Based on their outstanding bonding quality, bending strength, and biological durability, the study confirmed the feasibility of OPT plywood for marine applications.